Bride Price Valuation for Women with Disabilities: an Accounting Inquiry - Manehat, Beatrix Yunarti; Handayani, Suci Lestari; Sonbay, Yolinda Yanti; Brito, Manuel (Jurusan Akuntansi Politeknik Negeri Malang, 2025)
Purpose: Examines the basis of bride price through an accounting lens to support justice and inclusion for women with disabilities. Method: Qualitative approach using transcendental phenomenology Results: Bride price determination reflects not just economic value but also symbolism, power, and stigma, often marginalizing women with disabilities. Integrating accounting and social psychology, the need for inclusive reforms and critical valuation to promote justice in customary marriages. Novelty: Combining accounting and social psychology to critique injustice by viewing belis for women with disabilities as a socially charged number. Contribution: Supports policy reform with five recommendations for inclusive marriage practices for women with disabilities. Abstrak: Penilaian Mas Kawin bagi Perempuan dengan Disabilitas: Sebuah Kajian Akuntansi Tujuan: Mengkaji dasar penetapan belis melalui pendekatan akuntansi untuk mendukung keadilan dan inklusi bagi perempuan difabel. Metode: Pendekatan kualitatif dan metode fenomenologi transendental. Hasil: Penetapan belis tidak hanya soal nilai ekonomi, tetapi juga mencerminkan simbolisme, relasi kuasa, dan stigma yang meminggirkan perempuan difabel. Integrasi akuntansi dan psikologi sosial menyoroti perlunya reformasi inklusif dan refleksi kritis dalam praktik pernikahan adat. Kebaruan: Penggabungan akuntansi dan psikologi sosial untuk mengkritisi ketidakadilan melalui pembacaan belis sebagai angka yang sarat makna sosial bagi perempuan difabel. Kontribusi: Mendukung reformasi kebijakan melalui lima rekomendasi untuk menciptakan praktik pernikahan adat yang inklusif bagi perempuan difabel.